TRAINING ON THE UTILIZATION OF VEGETABLE PROTEIN SOYBEAN TEMPE AND PROCESSED TEMPE "SPICY TEMPE NUGGETS AND TEMPE PUDDING" IN KENDARI CITY - Yuli Purbaningsih; Sitti Aida Adha Taridala; Idrus Salam (International Journal of Engagement and Empowerment, 2021)
Soybean is an annual herb with branching dikotil little, the root system of a taproot, and cambium stem. Soybeans can turn into semi-vines in low light. Soy tempeh, which is not liked as food by the community, processed soybean tempeh, one of which is tempeh nuggets and tempeh pudding, has a very potential market, quite a lot of consumers support the development of this production which is an alternative food for people who want to consume products from tempeh flour. After we carry out all production activities, we continue to market it as the market potential in Southeast Sulawesi in particular, quite a lot of consumers support the development of this production which is a snack food for people who want to consume products from processed tempe products